Case Report: Investigation and characterization of a multiple endocrine neoplasia type 1 case and its pedigree - Liu, Yifan; Cui, Ling; Wang, Shiwei; Chen, Yanyan; Huang, Ting; Hou, Xin (Frontiers in Endocrinology, 2026)
Multiple Endocrine Neoplasia Type 1 (MEN1) is an autosomal dominant inherited disease characterized by the combined occurrence of tumors in multiple endocrine organs. As a rare disease, the clinical manifestations of MEN1 are currently considered to be associated with the development of combinations of more than 20 different tumors, such as parathyroid adenomas, neuroendocrine tumors, pituitary tumors, as well as lipomas, thymic carcinoids, pheochromocytomas, adrenal adenomas, and ovarian tumors. However, the concurrent occurrence of MEN1 and teratoma is extremely rare in reported cases to date. Herein, we report a case of a female patient with MEN1 who was diagnosed with teratoma. Genetic testing identified the NM_130799.2: c.512G>A (p.Arg171Gln) variant, which was classified as a variant of uncertain significance (VUS). After extracting whole blood DNA from the patient and her relatives (7 individuals in total) for genetic testing, this mutation was found to be present in multiple members of the family, including some who were affected by MEN1. This finding suggests the potential pathogenicity of the mutation, although further research and longer-term follow-up are required to confirm this observation.